2020
DOI: 10.1039/d0nj03080e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of noble metal Ag-modified BiVO4 nanosheets and a study on the degradation performance of tetracyclines

Abstract: The noble metal Ag Modified BiVO4 (Ag-BVO) composite photocatalytic was synthesized by photodeposition technology. The as-prepared photocatalyst was characterized by XRD, SEM, XPS, UV-vis DRS and electrochemistry measurement. The results...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…For Ag/BiVO4 system, it has been reported that superoxide radicals (O2 •-) are the main species involved in the degradation of organics. 69 To get an insight in the radicals involved in the case of the original 0.1 wt% NiOx(OH)y/BiVO4 photocatalyst, propan-2-ol (IPA), 1,4-benzoquinone (BQ) and potassium iodide (KI) were used as hydroxyl radical (OH • ), superoxide radical (O2 •-) and hole (h + ) scavengers, respectively for RhB photodecomposition. Then, photochemical sacrificial water splitting experiments were carried out to determine the ability of the different photocatalysts to promote O2 evolution reaction in the presence of an electron scavenger (sodium periodate).…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…For Ag/BiVO4 system, it has been reported that superoxide radicals (O2 •-) are the main species involved in the degradation of organics. 69 To get an insight in the radicals involved in the case of the original 0.1 wt% NiOx(OH)y/BiVO4 photocatalyst, propan-2-ol (IPA), 1,4-benzoquinone (BQ) and potassium iodide (KI) were used as hydroxyl radical (OH • ), superoxide radical (O2 •-) and hole (h + ) scavengers, respectively for RhB photodecomposition. Then, photochemical sacrificial water splitting experiments were carried out to determine the ability of the different photocatalysts to promote O2 evolution reaction in the presence of an electron scavenger (sodium periodate).…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…The presence of metallic Ag particles in Ag-BiVO 4 /BiOI significantly improved its PEC performance by promoting electron mobility, better visible light absorption and efficient separation of photogenerated electron–hole pairs through accelerated interfacial electron transfer by the formation of Schottky barrier which resulted in better percentage removal. In previous reports, researchers have also achieved enhanced degradation efficiencies of organics by incorporating Ag particles into BiVO 4 and other heterostructures 32 , 46 . The synergistic effect of light and applied potential in the PEC degradation process using the Ag-BiVO 4 /BiOI was also investigated and it was observed that both the photocatalytic degradation and electrochemical oxidation resulted in far less percentage removal of analyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag-BiVO 4 /BiOI photoanode was obtained through photodeposition of Ag. This was done by dipping the electrodeposited BiVO 4 /BiOI in a methanolic solution (50% v/v) of 0.1 M AgNO 3 in the dark for 30 min under continuous stirring which was followed by irradiation with a 100 W Xenon lamp (equivalent of 1.3 sun) for specified duration 32 . The samples were designated 1Ag-BiVO 4 /BiOI, 2Ag-BiVO 4 /BiOI and 3Ag-BiVO 4 /BiOI which corresponds to irradiation time of 15 min, 30 min and 45 min respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21]. In recent years, several synthetic materials that show heightened photocatalytic activity with noble metal acting as a cocatalyst have been manufactured, such as Au/BiVO 4 [22] and Ag/BiVO 4 [23]. However, the development is limited for the high price and shortage of noble metal.…”
Section: Introductionmentioning
confidence: 99%